Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1590/s0103-64402008000100013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ionizing radiation on rat parotid gland

Abstract: A common side effect of radiotherapy used in the treatment of oral cancer is the occurrence of structural and physiological alterations of the salivary glands due to exposure to ionizing radiation, as demonstrated by conditions such as decreased salivary flow. The present study evaluated ultrastructural alterations in the parotid glands of rats receiving a fractionated dose (1,500-cGy) of radiation emitted by a Cesium-137 source and rats that were not subjected to ionizing radiation. After sacrifice, the parot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 19 publications
2
14
0
2
Order By: Relevance
“…Table 1 The comparasion of severity of parotid histological damage among groups and number of mast cells In this study, radiation caused significant salivary gland injury as demonstrated by findings in the RT group, such as acinar shape defects, a partial loss of apical cytoplasmic material, considerable swelling and perinuclear vacuolization, and condensed-polymorphic nuclei in the acinar cells. These findings seem to be related to the induction of gland injury, consistent with other studies that utilized radiationinduced rat models (24)(25)(26). Moreover, increased malondialdehyde and TOS levels in the salivary glands were observed after 10 days of radiation administration.…”
Section: Discussionsupporting
confidence: 90%
“…Table 1 The comparasion of severity of parotid histological damage among groups and number of mast cells In this study, radiation caused significant salivary gland injury as demonstrated by findings in the RT group, such as acinar shape defects, a partial loss of apical cytoplasmic material, considerable swelling and perinuclear vacuolization, and condensed-polymorphic nuclei in the acinar cells. These findings seem to be related to the induction of gland injury, consistent with other studies that utilized radiationinduced rat models (24)(25)(26). Moreover, increased malondialdehyde and TOS levels in the salivary glands were observed after 10 days of radiation administration.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have shown that radiation can cause glandular epithelial damage (Cherry and Glucksmann, 1959;Frank et al, 1965;Elzay et al, 1969;Savage et al, 1985;Ahlner et al, 1993;Friedrich et al, 2002;Nagler, 2003;Radfar and Sirois, 2003;Vier-Pelisser et al, 2005;Boraks et al, 2008), leading to salivary gland hypofunction and xerostomia. It seems plausible that functional loss occurs by structural changes imposed on these tissues by radiation and, therefore, alterations occur in the parenchyma and stroma of these glands.…”
Section: Discussionmentioning
confidence: 99%
“…While significant levels of apoptosis immediately following radiation have been observed in mice [16,18-20], the presence of apoptosis in irradiated rats has been more variable [28-30]. Because acinar cells contribute a majority of saliva constituents including amylase and water, loss of these cells would impair normal saliva composition and lead to reduction in saliva flow.…”
Section: Discussionmentioning
confidence: 99%